Growth of venture firms under state capitalism with Chinese characteristics: Qualitative comparative analysis of fuzzy set - Kyung Hwan Yun; Chenguang Hu (Journal of Risk and Financial Management, 2023)
This study builds upon the venture growth literature and venture legitimation mechanisms and investigates how venture firms in China can acquire legitimacy and necessary resources from state stakeholders for venture growth during the COVID-19 pandemic. To offer a context-specific perspective of Chinese ventures' legitimation strategies, we discuss that under Chinese state capitalism, these ventures need to follow lingering socialist values, such as equality and social stability, to be recognized as appropriate business operations by state audiences. Furthermore, we discuss that access to necessary resources for venture growth is limited during crises. Based on the understanding of particular contexts of Chinese state capitalism and the COVID-19 pandemic, we examine how various sets of a venture's identity, associative, and organizational mechanisms influence venture growth during crises in China. In addition, we consider serial entrepreneurship as a contextual factor affecting the effectiveness of causal effects. This study applies the fuzzy-set qualitative comparative analysis method to take a configurational approach and identify multiple concurrent causality of legitimacy mechanisms on venture growth. We conduct a survey and analyze data from 107 entrepreneurs of Chinese technology ventures during the COVID-19 pandemic. Findings show that Chinese ventures with or without repeat entrepreneurs can actively utilize various sets of legitimation mechanisms to acquire legitimacy and necessary resources from Chinese state audiences for venture growth during adversity. This study provides comprehensive understanding and practical implications on Chinese ventures' legitimation strategies for venture growth during crises.
Keywords: 650; COVID-19; crisis management; fsQCA; state capitalism; venture growth; venture legitimation